1978
DOI: 10.1172/jci109024
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear (amplified) relationship between nuclear occupancy by triiodothyronine and the appearance rate of hepatic alpha-glycerophosphate dehydrogenase and malic enzyme in the rat.

Abstract: A B S T R A C T Three separate approaches were applied to examine the general relationship between R, the rate of induction of specific enzymes (mitochondrial a-glycerophosphate dehydrogenase and cytosolic malic enzyme) and q, the fractional nuclear occupancy by triiodothyronine in male Sprague-Dawley rats. Daily 200-,ug injections of triiodothyronine per 100 g body wt for 7 days resulted in saturation of the hepatic nuclear sites and the achievement of an apparent new steady state of enzyme levels. The increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
2

Year Published

1978
1978
2000
2000

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(41 citation statements)
references
References 33 publications
3
36
2
Order By: Relevance
“…would approximate previouis valtues on a regular diet (14). On the other hand, if the high CHO diet prodtuces maximal (juantities of 0 indepenident of(T3N), then Eq.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…would approximate previouis valtues on a regular diet (14). On the other hand, if the high CHO diet prodtuces maximal (juantities of 0 indepenident of(T3N), then Eq.…”
Section: Resultsmentioning
confidence: 94%
“…An increase in activity and mass of lipogenic enzymes also follows administration of thyroid hormone (9)(10)(11)(12). Moreover, previous studies from our laboratory have shown that the rate of lipogenic enzyme induction is related to nuclear occupancy in a nonlinear and highly amplified fashion (13)(14)(15). Thus, in the euthyroid state when approximately one half of the nuclear sites are occupied, the rate of ME induction is less than one-tenth of that which characterizes the response when the sites are fully occupied by triiodothyronine (T3).…”
Section: Introductionmentioning
confidence: 99%
“…This relationship, however, differed markedly from what we had observed in studies of the induction by T3 of hepatic mitochondrial a-glycerophosphate dehydrogenase (a-GPD) and cytosolic malic enzyme (decarboxylating) (ME) in the intact rat. In our studies, the number of detectable T3 nuclear-binding sites appeared to be independent of the level of T3 occupation (12), and the rate of enzyme induction was shown to become increasingly amplified with progressive nuclear occupancy by hormone (13). Thus, with full saturation of the nuclear sites, the rate of induction of a-GPD and ME was 10-18 times that observed under physiological conditions at which approximately one-half ofthe sites are normally occupied.…”
Section: Introductionmentioning
confidence: 43%
“…Because of the marked discrepancy between the occupancy-response relationships reported by Samuels et al (11) and by us (13), and because of the intrinsic biologic importance ofthe induction of pituitary GH by T3, we undertook a series of studies to analyze the kinetics of accumulation of pituitary GH in the intact hypothyroid rat. The mathematical model used in our analysis ofhepatic enzyme induction was applied to the pituitary GH data generated.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation